2009
DOI: 10.1063/1.3068459
|View full text |Cite
|
Sign up to set email alerts
|

Structure and lattice dynamics in PbTiO3–Bi(Zn1/2Ti1/2)O3 solid solutions

Abstract: ( 1 − x ) PbTiO 3 – x Bi ( Zn 1 / 2 Ti 1 / 2 ) O 3 solid solutions show a much enhanced tetragonality (c/a) and Curie temperature (TC). The detailed structure of (1−x)PbTiO3–xBi(Zn1/2Ti1/2)O3 is studied by means of neutron powder diffraction based on the Rietveld refinement. Zn exhibits a more polarizable property than Ti, resulting in a B-site cation splitting (0.27 Å) between Zn and Ti along c-axis direction. The spontaneous polarization displacements are enhanced by the substitution of Bi(Zn1/2Ti1/2)O3. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…In addition, Bi and Fe substitution creates greater localized disorder in the PZT lattice as noted by the diminished Raman spectrum intensity (figure 5). In a separate study, a similar decrease in Raman intensity has been observed in PbTiO 3 by co-doping with Bi and Zn [18].…”
Section: Resultssupporting
confidence: 48%
“…In addition, Bi and Fe substitution creates greater localized disorder in the PZT lattice as noted by the diminished Raman spectrum intensity (figure 5). In a separate study, a similar decrease in Raman intensity has been observed in PbTiO 3 by co-doping with Bi and Zn [18].…”
Section: Resultssupporting
confidence: 48%
“…[5][6][7] The crystal structures of the tetragonal solid solutions PbTiO 3 -BiFeO 3 and PbTiO 3 -BiZn1 =2 Ti1 =2 O 3 have been studied by Rietveld refinements using neutron powder diffraction data. [8][9][10][11] However, crystallographic mixed-site models provided little insight into displacements and coordination environments of the individual species, which precludes understanding a structural mechanism for accommodation of the anomalous lattice distortions. Attempts to introduce split sites for the octahedral cations (i.e., Fe and Ti or Ti and Zn) produced dubious results.…”
Section: Local Structure Underlying Anomalous Tetragonal Distortions mentioning
confidence: 99%
“…9 In a study of the x ¼ 0.3 member of the (1-x)PbTiO 3 -xBiZn1 =2 Ti1 =2 O 3 system, only a small fraction of the octahedral sites are occupied by Zn, which prohibited reliable separation of the Zn and Ti displacements. 10 The local structure of the tetragonal phase in the PbTiO 3 -BiZn1 =2 Ti1 =2 O 3 system has been analyzed using firstprinciples calculations. 11 The results suggested that Bi atoms are displaced more than Pb atoms, yielding shortest Bi-O distances of %2.2 Å , compared to %2.5 Å for Pb-O bonds.…”
Section: Local Structure Underlying Anomalous Tetragonal Distortions mentioning
confidence: 99%
“…The Curie point increases from 490°C for x = 0 to ~700°C in the same composition range. First principle studies have suggested that the large tetragonality in Bi(Zn 1/2 Ti 1/2 )O 3 results from strong coupling between the A‐site and B‐site cations induced by hybridization between the Zn 4 s , 4 p , and the O‐2 p orbitals . The high polarization along [001] direction along with a high Curie point makes this material a potential choice for next generation piezoelectric and nonvolatile memory applications.…”
Section: Introductionmentioning
confidence: 99%